P–577 Impaired double strand DNA repair in isolated Primary Ovarian Insufficiency with homozygous nonsense mutation of SPIDR. (6th August 2021) - Heddar, A; Guichoux, N; Auger, N; Misrahi, M
Abstract: Study question: To identify the etiology of isolated Primary Ovarian Insufficiency (POI) in a patient from an Indian consanguineous family. Summary answer: A homozygous nonsense mutation of SPIDR in the patient yielded chromosomal instability: first evidence of a role of this gene in DNA repair. What is known already: POI, affecting 1% of women under 40, is a public health problem. To date ∼ 70% of cases remain idiopathic. The leap due to exome sequencing, led to the identification of ∼ 80 genes, often in single or few cases. SPIDR was recently identified as a scaffolding protein connecting RAD51, a central player in homologous recombination, to BLM, a helicase implicated in the integrity of the genome. But its precise role is still unknown. A SPIDR mutation was previously associated with POI. However, contradictory conclusions were reported on the mechanism of SPIDR action and on its pathogenic role in POI. Study design, size, duration: Prospective genetic study of a cohort of 150 pateints with POI worldwide using a custom-made targeted next generation sequencing (NGS) panel comprising 60 known POI-causing genes. A single patient was found mutated in SPIDR. Cytogenetic studies were performed to analyse the consequences of the mutation on DNA repair and sister chromatide exchanges (SCE). Participants/materials, setting, methods: The patient with SPIDR mutation had POI with primary amenorrhea, delayed puberty and streaks ovaries. She was born to consanguineous Indian parents. No other mutation was detected in our cohort of 150 patients with POI. Targeted NGS was performed in the proposita. Familial segregation was performed by Sanger sequencing. Mitomycin C (MMC)-induced chromosomal breakages were studied and a sister chromatid exchange (SCE) assay was performed in patient's peripheral lymphocytes. Main results and the role of chance: We identified a novel homozygous nonsense mutation in the exon 7 of SPIDR (KIAA0146) c.814C>T, R272*, predicted to yield either a truncated protein, or a non-sense-mediated mRNA decay. The patient's cells display increased chromosomal fragility with high MMC-induced chromosomal breaks when compared to a control. Remarkably, there was no increased SCE. In the previous report of a SPIDR mutation in POI, no cytogenetic studies were performed, and contradictory results were obtained on a homologous recombination test between the two sisters, either enhanced or reduced. In conclusion, we show here that inactivation of SPIDR results in a defect of double strand DNA damage repair, similar to alteration of the RAD51 pathway. There was no increased SCE, the hallmark of the BLM pathway. This observation has major consequences for this patient's care : indeed mutations of DNA-repair genes may also yield to tumors/cancers. A long follow-up of the patient is needed in a multidisciplinary team to detect possible comorbidities. Indeed, even in the absence of somatic symptomatology, the patient has enhanced chromosomal instability highlighted by cytogenetic studies, that may yield tumor-predisposition. Limitations, reasons for caution: No other mutation of SPIDR in the replication cohort of 150 POI patients. SPIDR mutation are thus very rare world-wide. Wider implications of the findings: This is the first evidence of chromosomal instability associated with SPIDR defect, providing strong evidence for a role of SPIDR in double strand DNA damage repair in humans and for its causal role in POI. Our study improves the knowledge on SPIDR function and confirms its involvement in POI worldwide. Trial registration number: Not applicable